Posterior Tibial Slope: Effect on, and Interaction with, Knee Kinematics. Issue 4 (12th April 2016) - Ahmad, Riaz; Patel, Amit; Mandalia, Vipul; Toms, Andrew
Abstract : Posterior tibial slope should be measured on a long lateral or an expanded lateral radiograph. Posterior tibial slope decreases the quadriceps force needed to exert knee extension moment. Posterior tibial slope parallel to natural tibial slope minimizes tibial component subsidence. Posterior tibial slope should be increased rather than releasing the posterior cruciate ligament (PCL) to restore normal kinematics in a knee that is tight in flexion. Larger tibial slope widens the flexion gap in posterior stabilized total knee replacement.